The expression profile of platelet‐derived miRNA in coronary artery disease patients with clopidogrel resistance. Issue 2 (15th March 2021) - Lin, Shaoyi; Xu, Xiaofeng; Hu, Haochang; cheng, Ji; Chen, Ruoyu; Hu, Yingchu; Chen, Xiaomin
Abstract: Clopidogrel is widely used for antiplatelet therapy in patients with coronary artery disease (CAD), but clopidogrel resistance (CR) is relatively common in these patients. The goal of our study was to explore the platelet‐derived miRNA expression profile of CR in CAD patients. In this study, 66 CAD patients treated with dual antiplatelet therapy (clopidogrel 75 mg once daily plus aspirin 100 mg once daily) were included. According to inhibition of platelet aggregation (IPA), we divided these patients into CR group (IPA <30%) and control group (IPA ≥30%). The concentrations of clopidogrel and clopidogrel active metabolites in plasma were obtained using UHPLC‐Q‐Orbitrap HRMS method. The platelet‐derived miRNA expression profiles of these subjects were detected by high‐throughput sequencing and qRT‐PCR. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used for function prediction of differentially expressed miRNAs. Our results suggested no significant difference of clopidogrel and active metabolic derivative concentrations between CR group and control group. Correlation analysis showed no significant association between clopidogrel concentration and IPA; active metabolic derivative and IPA. In addition, 67 platelet‐derived miRNAs were differentially expressed between three CR and three control patients. After adjusting, eight miRNAs might be related to CR in CAD. In our validation cohort (30 CR patients and 30 control group), miRNA‐142‐3p and miRNA‐24‐3p expression levels were significantly upregulated, and miRNA‐411‐3p expression was significantly downregulated in the CR group. In conclusion, the miRNA‐142‐3p, miRNA‐24‐3p, and miRNA‐411‐3p might be potential markers for CR in CAD patients. Abstract : The platelet‐derived miRNAs in coronary artery disease patients with clopidogrel resistance.